Risk Factors of Perinatal Death Age 0-28 Days at RSD dr. Soebandi Jember - Ainindya Pasca Rachmadiani; Muhammad Ali Shodikin; Cicih Komariah (Journal of Agromedicine and Medical Sciences, 2018)
Abstract Perinatal deaths are babies who die at <28 days of birth. According to WHO, there are 2.7 million perinatal deaths worldwide in 2015. In 2016, the number of infant mortality at Jember is 50.19 per 1000 live births and become the second rank in Jawa Timur after Probolinggo. Infant mortality has been associated by maternal, gestational and neonatal factors. The aim of this study is to determine the risk factors of perinatal death age 0-28 days in RSD dr. Soebandi Kabupaten Jember. This research was analytic observasional with case control design doing in RSD dr. Soebandi Kabupaten Jember. The samples were 65 cases and 65 controls. Data analysis was done by Chi-square test and Fisher’s exact test with significance value < 0,05. The results showed APGAR Score (p <0.001, OR = 6.51), birth weight (p <0.001, OR = 9.66), body length (p <0.001 OR = 5.07), gestational age (p = 0.002; OR = 2.92), congenital anomalies (p = 0.013; OR = -) and maternal age (p = 0.001; OR = 4.51) were risk factors for perinatal death 0-28 days in RSD dr. Soebandi Kabupaten Jember. Keywords: perinatal deaths, neonatal factors, maternal factors, gestational factors.